Application of Quality Function Development (QFD) to Improve Quality and Develop Porang Rice Product XYZ - Pangastuti, Nova (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Porang rice is one of the alternatives to rice but porang rice producers are still very few and fairly new in the field. XYZ porang rice is one of the porang rice products that is quite in demand by various groups.  The purpose of this research is to provide information to companies to develop their products. Because developing this product requires the voice of consumers in the product development process with the hope that if the company develops the product in accordance with consumer expectations, an increase in sales will occur. So that later this XYZ brand porang rice can continue to improve its products and services for consumers. In this study, the steps taken at the beginning were to deepen the strengths and weaknesses of the product using the EFAS and IFAS matrices This study uses the Quality Function Development (QFD) approach with the initial stage of identifying customer needs and getting 19 attributes of consumer expectations of XYZ brand porang rice products. After that, a customer satisfaction performance (CSP) is made by comparing other brand products. related to determining the CSP value, the CSP value for XYZ Brand Porang Rice is 4.75 with a durable attribute within a day and the lowest is on a more creative and attractive product packaging model with a value of 2.35 while for its competitors with Shirataki Rice with the K brand, the attribute that has the greatest value is the high fiber and the size of the intact rice grains with a value of 4.70 and the lowest is the attribute of the packaging model with a variety of sizes, namely 1.45. Then processed into HOQ calculations and obtained the results of the 3 largest value of priority improvements in the production tool, then followed by marketing, and the third is in the texture produced.